Differential Inhibitor Sensitivity between Human Kinases VRK1 and VRK2 - Vázquez-Cedeira, Marta; Barcia-Sanjurjo, Iria; Sanz-García, Marta; Barcia, Ramiro; Lazo, Pedro A. (PLOS ONE, 2011)
Human vaccinia-related kinases (VRK1 and VRK2) are atypical active Ser-Thr kinases implicated in control of cell cycle entry, apoptosis and autophagy, and affect signalling by mitogen activated protein kinases (MAPK). The specific structural differences in VRK catalytic sites make them suitable candidates for development of specific inhibitors. In this work we have determined the sensitivity of VRK1 and VRK2 to kinase inhibitors, currently used in biological assays or in preclinical studies, in order to discriminate between the two proteins as well as with respect to the vaccinia virus B1R kinase. Both VRK proteins and vaccinia B1R are poorly inhibited by inhibitors of different types targeting Src, MEK1, B-Raf, JNK, p38, CK1, ATM, CHK1/2 and DNA-PK, and most of them have no effect even at 100 µM. Despite their low sensitivity, some of these inhibitors in the low micromolar range are able to discriminate between VRK1, VRK2 and B1R. VRK1 is more sensitive to staurosporine, RO-31-8220 and TDZD8. VRK2 is more sensitive to roscovitine, RO 31–8220, Cdk1 inhibitor, AZD7762, and IC261. Vaccinia virus B1R is more sensitive to staurosporine, KU55933, and RO 31–8220, but not to IC261. Thus, the three kinases present a different pattern of sensitivity to kinase inhibitors. This differential response to known inhibitors can provide a structural framework for VRK1 or VRK2 specific inhibitors with low or no cross-inhibition. The development of highly specific VRK1 inhibitors might be of potential clinical use in those cancers where these kinases identify a clinical subtype with a poorer prognosis, as is the case of VRK1 in breast cancer.